(untitled) (Bangladesh Journal of Pharmacology, 2016)
The aim of the present study was to investigate the effect of hydroalcoholic extract of Borago officinalis on morphine withdrawal syndrome in mice. Morphine-dependent group received morphine for nine days and then received naloxone via intraperitoneal injection. Control group received saline for nine days. Post-treated group received B. officinalis extract intraperitoneally (100 mg/kg) on the day 10 before naloxone injection. Co-treated group received B. officinalis extract intraperitoneally (100 mg/kg) and morphine for nine days and then received naloxone. Extract-treated group received extract for nine days and then received naloxone. Naloxone injection significantly increased the frequency of jumping, blinking, ptosis, defecation, paw trembling, and two-legged standing in comparison to the control group. Co-treatment and post-treatment with B. officinalis extract significantly decreased the withdrawal symptoms. In conclusion, hydroalcoholic extract of B. officinalis significantly attenuated the symptoms of morphine withdrawal syndrome. Video Clip of Methodology: 8 min 11 sec Full Screen Alternative